High dynamic range isotope ratio measurements using an analog electron multiplier. (25th June 2012) - Williams, P.; Lorincik, J.; Franzreb, K.; Hervig, R. L.
Abstract : We have explored measurement and accuracy issues in the use of an electron multiplier detector as a fast analog amplifier rather than in pulse‐counting mode. The electron multiplier on a Cameca IMS 3f instrument was modified to allow both analog and digital signals to be recorded simultaneously. The digital signal was picked up on the last dynode and the analog signal was recorded at the anode (operated near ground potential). The digital signal was differentiated to convert the positive pulse at the last dynode to a negative‐going signal that could be processed by the digital electronics of the IMS 3f and fed into the pulse counting system. The analog signal was amplified by an operational amplifier with a 10 6 ohm feedback resistor and the resulting signal was fed into the voltage/frequency convertor that normally processes the electrometer output from the Faraday cup collector. Isotope ratio measurements were explored for negative ion signals of the silicon and sulfur isotopes under Cs + primary ion bombardment. For 32 S and 34 S signals of 3 × 10 7 and 1.3 × 10 6 counts/s respectively and 1 s counting times for each isotope, the standard deviations of the means of 140 ratio measurements averaged 0.3 per mil. Measurements on two sulfide samples with isotope ratios previously determined to differ by 13.6 per mil were within 1.2 ± 0.5 per mil of the previous difference value. Sources of residual error are discussed. Copyright © 2012 John Wiley & Sons, Ltd.